(3GdhLjR aj EOGQI GdeDSSGJ GdEYdGejI (B/s - (3YHOdj, CMeOs; (3GSYjOGfj(B;(3abjQjs ((3GdLRGFQ (B:s (3OGQ GdNdOhfjI ,s, 2016)
(3JfGhd gPG GdcJGH HGNJUGQ MSf EOGQI GdeDSSI GdGYdGejI gj YUH Yed GdeDSSI h VGHWgG GdPj jfXe h jfSb h jJGHY h jTQa Ydi MSf SjQ GdYed GdGYdGej HgG h JTJed GdYedjI GdGOGQjI GdYOjO ef GdeYGjjQ CHQRgG af GdbjGOI (B, (3GSJQGJjLjI GdJNWjW (B, (3MSf GdQbGHI (B, (3gjcdI GdJfXje (B, (3YOe SdHjI GdJhXja (B, (3GdGJUGd GdOGFe(B, (3GdeTGQcI aj UfY GdbQGQ eY GdehXajf h CNjQG af GdJYGed eY GdBNQjf (B.s
Keywords: (3EOGQI GdeDSSGJ GdEYdGejIs; (3GdEYdGes; (3GdhLjR s